2007
DOI: 10.1682/jrrd.2006.12.0162
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain after spinal cord injury: What characteristics make some pains more disturbing than others?

Abstract: Abstract-Different types of pain are often present in the same individual with spinal cord injury (SCI). Relieving the most disturbing of these pains may substantially affect quality of life. Persons with SCI and chronic pain (n = 194) completed a structured interview that detailed the characteristics of each pain they experienced. Pairwise analyses revealed that the following characteristics were more common among the most disturbing pains: "sharp"; "stabbing"; located at the level of injury; frequently aggra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
4
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 61 publications
8
59
4
1
Order By: Relevance
“…First, most people with SCI experience three or fewer pain problems. 12 Second, describing the details of more than three different simultaneous pain problems may induce errors in the data collection due to increased assessment burden. Although the intent of the ISCIPDS:B is to evaluate each separate pain problem, it may also be used to evaluate the only most significant or 'worst' pain problem if there are severe time constraints.…”
Section: Description Of the Three Worst Pain Problemsmentioning
confidence: 99%
“…First, most people with SCI experience three or fewer pain problems. 12 Second, describing the details of more than three different simultaneous pain problems may induce errors in the data collection due to increased assessment burden. Although the intent of the ISCIPDS:B is to evaluate each separate pain problem, it may also be used to evaluate the only most significant or 'worst' pain problem if there are severe time constraints.…”
Section: Description Of the Three Worst Pain Problemsmentioning
confidence: 99%
“…Although loss of function is the main consequence of SCI, the symptoms experienced from the presence of such chronic pain could be so severe that it has been reported to frequently interfere with sleep and everyday activities [3]. To this end, approximately 37% of SCI patients reported that they would like to be relieved from this burden even if they had to trade it with additional loss of bladder, bowel, or sexual function [2].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their established usefulness and acceptance in assessing pain across various medical conditions [8,11,12], there have also been efforts to utilise the benefits of pain drawings to the SCI population that is characterised by the severity of this injury, which appears, for instance, in approximately more than 1,000 people per year in Britain alone [17]. To this end, [15] have used pain drawings to assess back pain and spinal deformity, whereas [4] attempted to identify and relieve the most disturbing pains in patients with a SCI that affect the quality of their life. Similarly, [5] utilised pain drawings before and after surgery to evaluate treatment interventions in SCIs.…”
Section: Current Approaches To Pain Visualizationmentioning
confidence: 99%
“…Reports from individuals who have suffered this kind of trauma reveal that the severity of such pain experience could be so immense that it often interferes with sleep and everyday activities [4]. In fact, a summary of results from several studies [see 16,19] indicates that the average reported estimate of the prevalence of chronic SCI pain is approximately 65%, with roughly one-third of those affected reporting the severity as greater than 7 in a scale of 10 on a Visual Analogue Scale (VAS).…”
Section: Introductionmentioning
confidence: 99%